Elaboración de instrumentos de evaluación para mejorar el proceso evaluativo en el área de lengua y literatura con un modelo emancipador en los séptimos años de educaciòn bàsica de la escuela “Juan Abel Echeverría” parroquia san buenaventura en el año lectivo 2012-2013 - Alomoto Chicaiza, Patricia Elizabeth (2013)
The carried out study consisted on providing technical and instruments of evaluation that contributes the development of the educational one and children of the school "JUAN ABEL ECHEVERRÍA" that presented as problematic the absence of Instruments of Evaluation with a Model Emancipador that impacted directly to the process evaluative. The importance of this investigation is to propose a dynamic alternative of evaluation that will facilitate to the educational one and niñ@s to the change of the perception of the valuation, in a reflexive way creating its own knowledge starting from technical as: salad of letters, crosswords, acrostics, conceptual maps, you debate in groups, etc. Before this situation the whole Institution manifested its unconditional support during the Elaboration of Instruments of Evaluation. The school "JUAN ABEL ECHEVERRÍA" when having the Elaboration of Instruments of Evaluation it frames transcendence in the life of the educational one, because he/she is projected to become a useful instrument to evaluate to the new generations of students, improving this way the quality of the education.